Evaluating symptom burden in kidney transplant recipients: validation of the revised Edmonton Symptom Assessment System for kidney transplant recipients – a single‐center, cross‐sectional study. (30th January 2020) - Dano, Sumaya; Pokarowski, Martha; Liao, Betty; Tang, Evan; Ekundayo, Oladapo; Li, Vernon; Edwards, Nathaniel; Ford, Heather; Novak, Marta; Mucsi, Istvan
Summary: We assessed the validity of the Edmonton Symptom Assessment System (ESAS‐r) in kidney transplant recipients (KTR). A cross‐sectional sample of 252 KTR was recruited. Individual ESAS‐r symptom scores and symptom domain scores were evaluated. Internal consistency, convergent validity, and construct validity were assessed with Cronbach's α, Spearman's rank correlations, and a priori‐defined risk group comparisons. Mean (SD) age was 51 (16), 58% were male, and 58% Caucasian. ESAS‐r Physical, Emotional, and Global Symptom Scores demonstrated good internal consistency (α > 0.8 for all). ESAS‐r Physical and Global Symptom Scores strongly correlated with PHQ‐9 scores (0.72, 95% CI: 0.64–0.78 and 0.74, 95% CI: 0.67–0.80). For a priori‐defined risk groups, individual ESAS‐r symptom score differed between groups with lower versus higher eGFR [pain: 1 (0–3) vs. 0 (0–2), delta = 0.18; tiredness: 3 (1–5) vs. 1.5 (0–4), delta = 0.21] and lower versus higher hemoglobin [tiredness: 3 (1–6) vs. 2 (0–4), delta = 0.27]. ESAS‐r Global and Physical Symptom Scores differed between groups with lower versus higher hemoglobin [13 (6–29) vs. 6.5 (0–18.5), delta = 0.3, and 9 (2–19) vs. 4 (0–13), delta = 0.24] and lower versus higher eGFR [11 (4–20) vs. 6.5 (2–13), delta = 0.21, and 7 (2–16) vs. 3 (0–9), delta = 0.26]. These data support reliability and construct validity of ESAS‐r in KTR. Future studies should explore its clinical utility for symptom assessment among KTR.